Vigor de sementes de soja na dinâmica do nitrogênio na planta e no desempenho da cultura em diferentes ambientes de cultivo - Escher, Jessica Aparecida Kafer (2024)
To obtain greater soybean productivity it is necessary to invest in quality seeds and promote cultivation in areas suitable for fertility. The aim of the work was to evaluate whether seed vigor and soil fertility interfere with nitrogen dynamics in plants and how much this impacts soybean productivity. The trials were conducted in the 2020/21 and 2021/22 crop years at the UTFPR Experimental Station, Campus Dois Vizinhos. The cultivar NS 4823 RR was used, in which the seeds were subjected to accelerated aging for 0, 24 and 48 hours at 40ºC, resulting in seeds with three levels of vigor. These were subjected to germination, accelerated aging, seedling length, germination speed index, electrical conductivity, and thousand seed mass tests. In the field, the contrasting seeds in force were sown in soils with different fertility histories, evaluating the plant stand, A, B and total chlorophyll, number of nodules and dry mass of nodules at stages R1, R3 and R5.2. In R8, productivity and nitrogen content in the grains were evaluated. Vigorous seeds generate more vigorous seedlings, which contribute to the maintenance of the plant stand and can positively influence the N dynamics in the plant and the productive performance of the crop. However, soil and climate conditions also have a strong influence on these processes.